Teleological vs. Scientific views of evolution theory among high school biology teachers in Argentina, Brazil, and Uruguay - Heslley Machado Silva; Robert A. Michaels; Gonzalo Pealoza; Graa S. Carvalho (Universitas Ahmad Dahlan, 2021)
This study explored the degree to which High School biology teachers in three Latin American countries embraced the religious concept of teleology or used it to motivate religious students to accept Darwinian evolutions scientific theory. The countries were (in increasing religiosity order): Uruguay, Brazil, and Argentina. We administered a one-item questionnaire to teachers in each country. It inquired how strongly teachers agreed or disagreed with the test statement: The emergence of the human species (Homo sapiens) was the aim of the evolution of living species. High School biology teachers acceptance and use of teleology was minimal in all three countries and related neither to their own religious beliefs nor to their countrys degree of religiosity. We followed up with interviews of a subsample of 10 participating teachers in each country. Interviews were interpreted using Collective Subject Discourse (DSC) analysis. Teachers in Argentina and Uruguay reported difficulty overcoming students anti-science attitudes, especially their anti-evolution attitudes. We conclude that improvement of pedagogical strategies is needed to motivate student acceptance of Darwinian evolution. Such strategies must appeal especially to students with highly religious upbringing, who disproportionately repudiate evolution and other scientific theories that are unpopular among highly religious people.